La politique de réconciliation nationale en Algérie : une approche sécuritaire - Mansour Kedidir (L’Année du Maghreb)
Since the end of the twentieth century, transitional justice has emerged as a set of mechanisms that can inspire countries in the prey to civil wars to find a way out of the crisis. However, depending on the specific contexts of each society and the identities of the protagonists, as well as their claims, the procedures vary, although they all seek a way out towards peace. Faced with a war between the National People’s Army and armed Islamic groups, Algeria has experienced a decade of insecurity, the effects of which were considerable in terms of human lives, material damage and the after-effects on the collective psyche. In order to restore peace and security, the government undertook a reconciliation process characterized by three phases: Clemency measures in the criminal field and two policies of civil concord and national reconciliation. The first aims at persons involved in terrorist actions who express their willingness to cease their criminal activities. It sets out two measures: exemption from prosecution and mitigation of penalties. The second and the third, which completes the process underway, are based on five axis: the people’s recognition of those responsible for safeguarding the Republic; measures to extinguish prosecutions, pardons and commutation of sentences; the socio-professional reintegration of those responsible for the ‘national tragedy’; taking care of those who have disappeared; and strengthening national cohesion. In view of the army’s perception of the terrorist threat, the nature of the mechanism adopted in the process, its temporalities and its modus operandi, the reconciliation policy seems s to be part of a security approach. In order to discuss this hypothesis, this article will go in two directions: the imperative of restoring peace and ordered forgetting.